The future of the nation foretold in its museums. (August 2014) - Lebovics, Herman
With the opening of several new musées de la société in France we gain an exceptionally rich and revelatory way of understanding the society-wide debates about what France is and what it should be in the new millennium. Each of the museums discussed offers pieces of the contested stories of a new France in a new age. Taken together, they ask whether it is possible, or even desirable, today to tell a single and teleological national narrative, the roman national of the patriot-historians of the Third Republic. What did immigrants contribute to the making of today's nation? What is the relationship of postcolonial France to its one-time colonial empire? How did biological and cultural evolution combine to make human societies? And now, with the opening of the Musée des Civilisations de l'Europe et de la Méditerranée, how did, and how do, French vernacular cultures relate to those of Europe and the Mediterranean world? The article argues that a way of understanding this complex of questions is to follow the stories that the new museums tell – or the disagreements about what stories they ought to tell. For these questions go to matters of high state policy, international economic interests, cultural outreach, the relations of regions to capitals, tourism, and indeed claims about what it means to be French today.